(untitled) - Lau, Vincent K. N. (Hoboken, N.J., 2006)
The book is divided into three parts, first giving readers a good foundation in underlying theory, then exploring applications as well as advanced topics: Part 1 examines theoretical aspects of channel adaptation in wireless communications for point-to-point and multi-user systems with multiple antennas; Part 2 focuses on the applications of the channel-adaptive technologies in practical systems such as UMTS; Part 3 delves into topics such as multi-user scheduling for wideband systems, combined queuing theory and information theory, and ad hoc routing
Keywords: Wireless communication systems,Hệ thống truyền thông không dây; Design and construction,Thiết kế và xây dựng